2017
DOI: 10.5603/kp.a2016.0162
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cardiovascular risk in patients undergoing total joint alloplasty: the CRASH-JOINT study

Abstract: A b s t r a c tBackground: Risk assessment is of particular importance for patients undergoing surgical interventions. Orthopaedic procedures, especially total joint alloplasty, are major procedures associated with high perioperative risk, as well as one of the highest rates of complications. Aim:The aim of the present study was to establish the prevalence of classical and non-classical cardiovascular risk factors in patients undergoing total hip or knee alloplasty. Methods:The CRASH-JOINT (Cardiovascular Risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The Cardiovascular Risk Assessment ScHeme in JOINT arthroplasty study (CRASHJOINT) revealed the relatively high prevalence of both classical as well as nonclassical cardiovascular risk factors in patients undergoing total hip or knee replacement, and showed that those fac tors are more common than in the general population [15]. In the study, we found that out of 98 patients, eight patients were excluded from the study and surgery, mainly due to cardiac causes.…”
Section: The Importance Of Cardiovascularmentioning
confidence: 77%
See 2 more Smart Citations
“…The Cardiovascular Risk Assessment ScHeme in JOINT arthroplasty study (CRASHJOINT) revealed the relatively high prevalence of both classical as well as nonclassical cardiovascular risk factors in patients undergoing total hip or knee replacement, and showed that those fac tors are more common than in the general population [15]. In the study, we found that out of 98 patients, eight patients were excluded from the study and surgery, mainly due to cardiac causes.…”
Section: The Importance Of Cardiovascularmentioning
confidence: 77%
“…As was mentioned previously [15], the oc currence of cardiac complications after surgery depends on the risk factors of the patient and the type of operation [16]. Each operation triggers a stress response that is initiated by tissue damage, developed with the participation of neuro endocrine factors, and may cause a sympathetic imbalance resulting in myocardial oxygen consumption increase, and an imbalance between prothrombotic factors and fibrinolytic factors.…”
Section: Methods For Cardiovascularmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been no previous research on cardiac referral for the asymptomatic preoperative TJA population in which cardiac disease not yet exhibiting clinical manifestation but capable of contributing to risk of postoperative cardiac complication may exist. Over-referral is unsustainable [ 4 , 22 24 ] and may unnecessarily delay surgery [ 25 , 26 ]; however under-referral may lead to missed pre-operative optimisation for asymptomatic patients who otherwise would have benefited, and may contribute to post-operative cardiac complication.…”
Section: Discussionmentioning
confidence: 99%
“…These factors include a strong family history of early-onset CVD, milder degrees of impaired glucose regulation, low-density lipoprotein cholesterol, triglycerides, or fibrinogen [5]. Newer studies suggest also the impact of obstructive sleep apnoea, erectile dysfunction, depression and anxiety, air pollution, and periodontal disease as potent cardiovascular risk factors (Table 1) [18][19][20][21][22][23][24]. 15% and more 10-14% 5-9% 3-4% 2% 1% < 1% 9 11 13 16 18 6 8 9 11 13 5 5 6 8 9 3 4 5 5 6 4 4 5 6 8 3 3 4 4 5 2 2 3 3 4 1 1 2 2 3 7 8 10 12 14 5 6 7 8 10 3 4 5 6 7 2 3 3 4 5 5 6 7 8 9 3 4 5 6 7 2 3 3 4 5 2 2 2 3 3 2 2 3 3 4 1 2 2 2 3 1 1 1 2 2 1 1 1 1 1 5 6 8 9 11 4 4 5 6 7 3 3 4 4 5 2 2 3 3 4 3 4 5 5 7 2 3 3 4 5 2 2 2 3 3 1 1 2 2 2 1 2 2 2 3 1 1 1 2 2 1 1 1 1 1 1 1 1 1 0 5 6 7 8 9 3 4 5 5 7 2 3 3 4 5 2 2 2 3 3 3 3 4 4 5 2 2 3 3 4 1 1 2 2 3 1 1 1 1 2 2 2 2 3 3 1 1 2 2 2 1 1 1 1 2 1 1 1 1 1 1 1 1 1 1 1 1 1 1 0 1 1 0 0 0 0 0 0 0 0…”
Section: Shortcomings Of the Score Risk Chartsmentioning
confidence: 99%